PENGEMBANGAN PARIWISATA HALAL: EKONOMI BIRU BERBASIS KEARIFAN LOKAL DI PROVINSI LAMPUNG, INDONESIA - Mardhiyah Hayati; Mad Heri (IQTISHODUNA: Jurnal Ekonomi Islam, 2025)
The Blue Economy is part of socio-economic and development activities, aiming to prevent environmental degradation by optimizing the benefits derived from marine resources. The purpose of this study is to explore the interaction between the blue economy and local wisdom in the development of halal tourism in Lampung province. This study uses primary data sources and a narrative Literature Review related to halal tourism, blue economy, and local wisdom. The research found that several things can be done in the development of halal tourism in the implementation of the blue economy based on local wisdom, namely: 1) community participation is the main driver of tourism development and progress through the implementation of the blue economy which refers to the social and cultural of the local community (local wisdom); 2 the provision of halal-based facilities and services is important in order to attract Muslim tourists; 3) destination managers must provide accurate information related to halal services; 4) improve service quality by encouraging tourism employees to increase awareness, knowledge, and skills in providing halal-based services; 5) natural environment problems cannot be solved technically, appropriate solutions are needed to change human mentality and awareness in environmental management to remain sustainable, so good cooperation between the community, tourism managers and the government is needed.